The association of the paraoxonase 1 Q192R polymorphism with coronary artery disease (CAD) and cardiometabolic risk factors in Iranian patients suspected of CAD - Darand, Mina; Salehi-Abargouei, Amin; Vahidi Mehrjardi, Mohammad Yahya; Feizi, Awat; Seyedhossaini, Seyed Mustafa; Askari, Gholamreza (Frontiers in Cardiovascular Medicine, 2023)
Introduction The present study aimed to investigate the association of the paraoxonase 1 (PON1) Q192R polymorphism with coronary artery disease (CAD) and cardiometabolic risk factors in Iranian patients suspected of CAD. Methods This cross-sectional study was conducted on 428 patients undergoing angiography. The data related to demographic information and physical activity were collected by valid and reliable questionnaires. The PON-1 genotypes were detected by the polymerase chain reaction-restriction fragment length polymorphism (RFLP-PCR) technique. The Gensini and SYNTAX score, anthropometric measurements, and biochemical and clinical parameters were measured by standard protocols. Results and discussion Findings indicated that the odds of obesity was significantly higher in people with the RR genotype compared to the QQ genotype carriers (OR: 2.95 CI: 1.25–6.93, P = 0.014) and also odds of low high-density lipoprotein cholesterol (HDL-C) was marginally higher (OR: 2.31 CI: 0.97–5.49, P = 0.056). There was no significant association between other CAD risk factors with PON1 Q192R polymorphism (P > 0.05). Further analysis showed a significant interaction between sex and 192QR (P = 0.019) and 192 RR (P = 0.007) genotypes on body mass index (BMI). More specifically, the risk of obesity in men carrying the RR genotype was 3.38 times (OR: 3.38 CI: 1.08–10.58, P = 0.036). Also, a significant joint effect of the RR genotype and sex on HDL-C was seen (P = 0.003). The stratification based on sex showed that the risk of low HDL-C is significantly higher in women carrying the RR genotype (OR: 6.18 CI: 1.21–31.46, P = 0.028). A marginal sex-genotype interaction was also found in the risk of elevated alanine aminotransferase (ALT) (P = 0.057). In summary, the findings showed that the risk of obesity and low HDL-C was higher in people carrying the RR genotype. On the other hand, a Q192R polymorphism-sex interaction was observed on the risk of obesity, elevated ALT, and low HDL-C.